2009
DOI: 10.1159/000196280
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Measuring Soluble Receptor Activators of Nuclear Factor-κB Ligand and Osteoprotegerin in Bone Metabolism of Elderly Women

Abstract: Background/Aim: The discovery of a signaling system consisting of a soluble receptor activator of the NF-κB ligand (sRANKL) and its decoy receptor osteoprotegerin (OPG) has provided a valuable key to understanding the pathophysiology of the bone microenvironment. We conducted a cross-sectional study of the role of sRANKL and OPG levels as they relate to bone metabolism in elderly postmenopausal women with and without osteoporosis. Subjects and Methods: Fifty-one elderly women with or without osteoporosis were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…These findings are discussed to reflect an increased pool of osteoblasts or osteoblast precursor cells, which produce OPG; some authors explain the OPG increase as a response of bone to the elevated turnover status in order to normalize it. Again, data remain controversial, as there are some papers that failed to prove any association of OPG with turnover markers [43][44][45].…”
Section: Effects Of Age Gender and Body Mass Index (Bmi) On Serum Omentioning
confidence: 99%
See 2 more Smart Citations
“…These findings are discussed to reflect an increased pool of osteoblasts or osteoblast precursor cells, which produce OPG; some authors explain the OPG increase as a response of bone to the elevated turnover status in order to normalize it. Again, data remain controversial, as there are some papers that failed to prove any association of OPG with turnover markers [43][44][45].…”
Section: Effects Of Age Gender and Body Mass Index (Bmi) On Serum Omentioning
confidence: 99%
“…The Danish twin studies revealed only a small weak correlation of OPG and sRANKL with BMD in a healthy population [28]. In patients with osteoporosis, there was an inverse relation between OPG and BMD [18,24,27,39,44,[46][47][48][49] a fact that is commonly interpreted as reduced OPG (and mineral) content in osteoporosis; yet, some authors described a positive correlation between OPG and BMD [25,42,45] as a kind of endogenous protective mechanism against bone loss. Serum RANKL levels seem to be independent of BMD [18,27,30,50].…”
Section: Effects Of Age Gender and Body Mass Index (Bmi) On Serum Omentioning
confidence: 99%
See 1 more Smart Citation
“…However, the literature presents conflicting results concerning the period after menopause, when bone loss is related to favoring RANKL activity over that of OPG. In a cohort study, Mezquita-Raya et al 21 and Chiba et al 22 found no correlation between OPG and bone resorption markers in women, regardless of their menopause status. According to the results, this study also demonstrated that the expression of bone markers during repair of autogenous bone grafts was not altered by estrogen deficiency.…”
mentioning
confidence: 93%
“…Stern et al found that the plasma level of RANKL rose significantly with age and was inversely associated with BMD in men only 17. In contrast, a number of studies have been unable to demonstrate any significant correlation between serum RANKL and BMD in postmenopausal women 14 18 19…”
Section: Introductionmentioning
confidence: 99%